Design a Blog Web Creation Application Using HTML 5 - Rizaldy Khair; Ekatri Ayuningsih (Sean Institute, 2020)
The purpose of this study is to simplify the process of creating a weblog and provide solutions to compatibility problems in standalone applications. HTML5 is the latest web technology that continues to be developed and will soon be the successor of the previous generation of HTML. The web-based presentation creation service in question will utilize HTML5 and JavaScript features to present a user-friendly web-based application, with an emphasis on receiving input in the form of text and managing it into a web 2.0-based responsive blog. This web2.0 blog based on HTML 5 and CSS 3 provides a presentation creation interface with features such as automatic audio and video player without having to add additional plugins. In addition, this blog simplifies in the creation of coding.